2019
DOI: 10.1039/c9nr04461b
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled carbon nanoparticles as messengers for artificial chemical communication

Abstract: Herein, supramolecular carbon nanoparticle aggregates were obtained and used as messengers for molecular communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…They are characterized by high optical and chemical stability, good water solubility, photobleaching resistance biocompatibility, and low-cost preparation. For these reasons, nowadays CNPs found application in a wide range of fields, such as analytical chemistry, biosensing, bioimaging, theranostics, molecular communication, and photocatalytic energy conversion …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are characterized by high optical and chemical stability, good water solubility, photobleaching resistance biocompatibility, and low-cost preparation. For these reasons, nowadays CNPs found application in a wide range of fields, such as analytical chemistry, biosensing, bioimaging, theranostics, molecular communication, and photocatalytic energy conversion …”
Section: Results and Discussionmentioning
confidence: 99%
“…They are characterized by high optical and chemical stability, good water solubility, photobleaching resistance biocompatibility, and low-cost preparation. For these reasons, nowadays CNPs found application in a wide range of fields, such as analytical chemistry, 35 biosensing, 36 bioimaging, 37 theranostics, 38 molecular communication, 39 and photocatalytic energy conversion. 40 Our strategy is to combine the recognition properties offered by the "multitopic approach" with the water solubility and the excellent optical properties of CNPs, in order to obtain a new generation of nanostructured water-soluble sensors for the efficient and selective detection of CWAs in water and gas phases.…”
Section: Resultsmentioning
confidence: 99%
“…Cell toxicity tests show a low degree of toxicity and good biocompatibility [ 16 , 17 ]. The use of carbon-based CQD in MoCo applications derives mainly from their unique fluorescence properties [ 4 , [18] , [19] , [20] , [21] ]. Indeed, most of these CQD have an absorption band in their UV spectra (observed at 200–400 nm) and a fluorescence band in their visible spectrum (observed at 400–600 nm).…”
Section: Information Nanoparticlesmentioning
confidence: 99%
“…The name CDs, therefore, reflects the composition and property of emitting light at different wavelengths from the incident. Since their discovery by Xu et al in 2004, CDs have been applied for different basic research circumstances and very technical applications ranging from molecular communication to theranostics, as well as for the detection of specific analytes , with particular reference to metal ions. Moreover, as demonstrated by Sun et al, CD fluorescence yield is greatly increased through surface passivation . Although the chemical–physical mechanism underlying CD fluorescence is not yet fully understood, it is found in the literature that fluorescence can be modulated through several factors: particle size (quantum effect), surface groups, surface defects, and fluorophores with different degrees of π conjugation and electron holes located between the sp 2 carbons of the clusters and the sp 3 carbons of the matrices. Recent studies have shown that the optical properties vary considerably depending on the synthesis methodology used, passivation, doping, and size of the CDs. This suggests that fluorescence may depend on the surface of the nanoparticles, in particular on the ″surface defects″ that may be responsible for absorption at certain wavelengths .…”
Section: Introductionmentioning
confidence: 99%